KEANEKARAGAMAN JENIS HERPETOFAUNA (ORDO SQUAMATA) DI KAWASAN BUKIT WANGKANG HUTAN LINDUNG GUNUNG AMBAWANG KABUPATEN KUBU RAYA - Sarjoko, Nanding; Rifanjani, Slamet; Wahdina, . (JURNAL HUTAN LESTARI, 2018)
Gunung Ambawang was protected area including lowland forest type and plantation area border. The activities found to built plantation acces and changing the plantation oil and plantation rubber area to be effect the Biodiversity species of reptile. The purpose of the research to knowed Biodiversity species and measure Herpetofauna (Ordo Squamata)Â  abundant species in Gunung Ambawang protected areaÂ  Kubu Raya Regency. The method used Visual/VES (Visual Encounter Survey) combination with transect system on the two types that was Aquatic and Teresterial (Kusrini, 2008). The survey consisted of 5 transect that length at 1 km. The results showed that Reptile species was found in 12 species , that were classified into 6 family, 4 Lizards (Sauria) family, and 2 Snakes (Ophidia). The Biodiversity teresterial habitat was found with the highest of species were 9 species. Whereas Aquatic habitat was found with the greatest number which 12 cyrtodoctylus yoshii individual.Keywords : Diversity, Herpetofauna, Kubu Raya Regency, Protected forest